Exploring the Scientific Rationality of the Phenomenon of “Different Dosage Forms of the Same Prescription” of Chinese Proprietary Medicine Based on Biopharmaceutical Properties of Powder and Pill of Chuanxiong Chatiao Prescription - Qu, Zhong-huan; Liu, Lin; Zhang, Xiao-fei; Guo, Dong-yan; Zhai, Bing-tao; Zou, Jun-bo; Shi, Ya-jun (Frontiers in Pharmacology, 2022)
Background: The 2020 edition of the Pharmacopoeia of the People’s Republic of China (Chinese Pharmacopoeia 2020 edition) has 255 Chinese prescriptions with different dosage forms, accounting for 21.09% of the total prescriptions (1,209) in Chinese Pharmacopoeia 2020 edition. However, the scientific rationality of the phenomenon of “Different Dosage Forms of the Same Prescription” of Chinese proprietary medicine has been less explored. Based on the dosage form theory of “components in pills release slowly and take effect in slow-acting manner, while in powders release quickly and take effect in fast-acting way,” we provided the in vitro dissolution experiment and in vivo pharmacokinetics of Chuanxiong Chatiao powders and pills in order to rationalize the phenomenon of “Different Dosage Forms of the Same Prescription” of Chuanxiong Chatiao prescription. Materials and Methods: Chuanxiong Chatiao powders and pills were prepared in the laboratory referring to the preparation methods in the Chinese Pharmacopoeia 2020 edition, and the contents of tetramethylpyrazine, ferulic acid, nodakenin, and isoimperatorin were determined by the external standard method. We measured the in vitro dissolution of four analytes of Chuanxiong Chatiao powders and pills according to the second method for dissolution determination (paddle method) in the Chinese Pharmacopoeia 2020 edition, and their corresponding contents in each sampling point were determined by LC-MS/MS. We also provided a pharmacokinetic study of Chuanxiong Chatiao powders and pills. Six female domestic rabbits were divided into two groups (powder and pill groups) and given Chuanxiong Chatiao powders and pills (9.85 g/kg) by surgical administration separately. Blood samples were collected at 5, 15, 30, 45, 60, 90, 120, 150, 180, 240, 360, 480, 720, and 1,440 min after drug administration to measure the plasma concentration of the four analytes by LC-MS/MS. Results: The results of in vitro dissolution experiment showed that the dissolution rate of four analytes in the powder group was greater than that of the pill group. However, the solubilities of tetramethylpyrazine and isoimperatorin were very low in the powder and pill, which may be related to their low solubility properties. The results of the in vivo pharmacokinetic study of Chuanxiong Chatiao powders and pills showed that Tmax (h) of ferulic acid and nodakenin in the powder group was 0.420 and 0.053 times that of the pill group and t1/2 (h) of ferulic acid, nodakenin, and isoimperatorin of the powder group was 0.910, 0.262, and 0.661 times that of the pill group, respectively. Conclusion: The in vitro dissolution rate and in vivo pharmacokinetic parameters of four analytes in CXCTF could partly explain the scientific rationality of the classic theory of “丸者缓也, 散者散也” as in Chinese, which is helpful for providing a basis for the comparison of subsequent dosage forms. The results of our studies also suggest the complexity of the design of dosage forms of Chinese proprietary medicines and imply that we should pay more attention to the scientific rationality of the phenomenon of “Different Dosage Forms of the Same Prescription.”